Damage-free Structural and Optical Characterization for InGaN/GaN Multi-Quantum Well Epi-Layers - Joon Yoon, Young; Kim, Mi-Yang; Seop Kwak, Joon (Asian Journal of Chemistry, 2013)
The quality of InGaN/GaN multi-quantum wells, especially the uniformity of composition and thickness, can have a strong influence on carrier localization and it will finally determine the probability of radiative recombination and internal quantum efficiency. However, characterizing the structural properties of multi-quantum wells in an atomic level remains a difficult task, because other existing techniques for measurement of ultra-thin layer are limited in spatial resolution and sensitivity. In addition, analytical artifacts frequently occur in the results from electron microscopy caused by irradiation from the high energy incident beam. To overcome the limitations of the analysis of InGaN/GaN multi-quantum wells for light emitting diodes, high-resolution scanning transmission electron microscopy technique was employed. It was possible to measure both the strain field and indium atom distributions in InGaN/GaN multi-quantum wells without the electron damage. In addition, the new formula was employed to describe the temperature dependence of the integrated photoluminescence intensity from the multi-quantum wells to estimate internal quantum efficiency.